Design and Analysis of a Passive Lighting Device for a Sustainable Office Environment in Hot-Arid Climate Conditions - Daich, Safa; Saadi, Mohamed Yacine; Daiche, Ahmed Motie (International Journal of Sustainable Construction Engineering and Technology, 2022)
Visual comfort in office spaces improves not only productivity and wellbeing but also satisfaction and energy efficiency of the buildings. The objective of this research is to study the effect of one of the transporting daylighting systems (Anidolic Integrated Ceiling ‘AIC’) on the enhancement of the luminous interior environment and energy saving in office building through objective and subjective evaluations. The quantitative study was performed by measurement of the illuminance values in the physical model (1:4) under local luminous climate in two scenarios (with and without ‘AIC’) and by numerical simulation to calculate the daylight autonomy. The qualitative evaluations were achieved by using a field survey composed of four questions related to pleasantness, level of light and artificial lighting needs. Experimental study shows that the AIC offers high levels of illumination in quantitative terms result in moderate values of Daylight Factor (2% - 4%). Simulation results showed that more than 88% of energy consumption for electrical lighting can be saved. Subjective evaluation results indicate that in the test model (with AIC), 67% of participants felt more pleasant with the luminous environment, 74.19% considered that the level of light is sufficient and only 08 of 31 subjects need to use artificial lighting.